Track structure of protons and other light ions in liquid water: Applications of the LIonTrack code at the nanometer scale. Issue 6 (10th May 2013) - Bäckström, G.; Galassi, M. E.; Tilly, N.; Ahnesjö, A.; Fernández‐Varea, J. M.
Abstract : Purpose: The LIonTrack (Light Ion Track) Monte Carlo (MC) code for the simulation of H +, He 2+, and other light ions in liquid water is presented together with the results of a novel investigation of energy‐deposition site properties from single ion tracks. Methods: The continuum distorted‐wave formalism with the eikonal initial state approximation (CDW‐EIS) is employed to generate the initial energy and angle of the electrons emitted in ionizing collisions of the ions with H2 O molecules. The model of Dingfelder et al. ["Electron inelastic‐scattering cross sections in liquid water, " Radiat. Phys. Chem., – (1998)10.1016/S0969‐806X(97)00317‐4 ; Dingfelder et al. "Comparisons of calculations with PARTRAC and NOREC: Transport of electrons in liquid water, " Radiat. Res., – (2008)10.1667/RR1099.1 ] is linked to the general‐purpose MC code PENELOPE/penEasy to simulate the inelastic interactions of the secondary electrons in liquid water. In this way, the extended PENELOPE/penEasy code may provide an improved description of the 3D distribution of energy deposits (EDs), making it suitable for applications at the micrometer and nanometer scales. Results: Single‐ionization cross sections calculated with the ab initio CDW‐EIS formalism are compared to available experimental values, some of them reported very recently, and the theoretical electronic stopping powers are benchmarked against those recommended by the ICRU. The authors also analyze distinct aspects of the spatial patterns of EDs, such as the frequency of nearest‐neighbor distances for various radiation qualities, and the variation of the mean specific energy imparted in nanoscopic targets located around the track. For 1 MeV/u particles, the C 6+ ions generate about 15 times more clusters of six EDs within an ED distance of 3 nm than H + . Conclusions: On average clusters of two to three EDs for 1 MeV/u H + and clusters of four to five EDs for 1 MeV/u C 6+ could be expected for a modeling double strand break distance of 3.4 nm.